Efektivitas Kata-kata Kutukan sebagai Retorika dalam Komunikasi Perubahan Perilaku: Kajian Makro Linguistik - M. Yanuardi Zain; Zuriyati Zuriyati; Saifur Rohman (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2022)
Communication style or rhetoric plays an essential role in helping a person to deliver a message effectively. Therefore, someone will use an appropriate rhetoric in communication based on the characteristics of the message recipient. However, regardless to the style used, everybody has the same purpose in communication that is how to change the people’s behavior when they receive the message. The study is aimed at exploring the effectiveness of using cursing words as communication style to change people’s behavior in disposing of garbage. Descriptive qualitative analysis with open-ended questions was applied in semi-structure interview to a garbageman and local person to explore the effectiveness of cursing words as communication style to change human’s behavior. The result showed that the words give good impact in changing human’s behavior which is proved by the reduce of garbage volume thrown by the people in the area where the banner of cursing words installed. Furthermore, if the banner is damaged, the habit of the people to throw garbage in the area will increase.